ANALYSIS OF RESEARCH RESULTS ACCORDING TO INTERNATIONAL STANDARDS - Abdullayev, Ravshan; Azambayev, Muxammadjon; Baxritdinov, Sayfuddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article provides analyses after conducting scientific and practical research on international and universal standards of cotton fiber. And also, methods, definitions and designations of studies are considered, both the class method and the HVI laboratory system. The classification of mediumfiber cotton fiber according to American universal standards is considered.